A genetic imaginary for social justice: The rhetoric of genomic medicine as exceptional, ordinary, and ethical obligation - Kasia Tolwinski; Diana Madden; Jennifer K. Wagner (Elsevier, 2022)
We interviewed professionals and stakeholders in genomic medicine to understand how they envision their field and argue for its importance. Their rhetoric constitutes a shared "genetic imaginary" where genomic medicine is at once exceptional, ordinary, and an ethical obligation. Genomic medicine is argued by our interviewees to be exceptional by virtue of novel scientific knowledge it offers and the resultant effects on clinical practice; ordinary in that it is just another way of understanding the body that leads straightforwardly to the evolution of healthcare; and an ethical obligation because it provides comprehensive insight and care that should be accessible to all people. Despite desires to make genomic medicine diverse, inclusive, and accessible - envisioning it working as a matter of social justice - we argue that there are structural constraints that impede this genetic imaginary from becoming a reality. We argue that genomic medicine must be actively shaped in ways that foster social justice so as not to perpetuate current and historical disparities in medicine.